Modified Engine Locking System Through Alcohol Detection - P. Prakash, B. Sravan Kumar, G. Saisravanthi, M. Madhu Babu, G.V.S.S. Siva Kumar (Mathematical Statistician and Engineering Applications, 2023)
In this project, an alcohol detection system with engine locking for vehicles is set up and put into operation. It uses an ultrasonic sensor and an Arduino UNO as the MCU (Master Control Unit). The system will accurately detect the alcohol concentration in the alcohol disclosure sensor and, in the event that it is beyond the threshold level, will turn off the vehicle’s engine. A reliable LCD will display the alcohol content. The model will similarly communicate the location of the car. The project gives a strong defence against disasters under control brought on by smashed driving.